A luta internacional dos trabalhadores em educação: um estudo sobre os sindicatos em educação pública da fronteira Brasil-Paraguai-Argentina. - Kasper, Sandra Regina Severo (2017)
This máster thesis delimits the comparative study of the structures of formal organization of unions in education of the Brazil-Paraguay-Argentina border, with the general objective of verifying if there is evidence of internationalist articulation among unions of public education workers in this region. The cut of the comparative study occurred in the formal organizational structures of the National Union of Educators, National Union, Ciudad del Este-Alto Paraná-Paraguay Base Committee (hereinafter UNE-SN-CDE), APP- Union of workers in education (hereinafter referred to as APP-FI) and the Union of Teachers of the Province of Misiones (hereinafter UDPM-PI), the Trade Union Department of Puerto Iguazú-Misiones-Argentina. The central question of this study was: do the formal structures of these unions reveal evidence of internationalist initiatives among workers' unions in the education of the Foz do Iguaçu-Brazil, Ciudad del Este-Paraguay and Puerto Iguazú-Argentina frontiers? What are the similarities and differences in the formal organizational structures of these unions? The initial understanding is that these unions had in common the territorial proximity, given by the Brazil-Paraguay-Argentina border. We chose as method of research the Historical Dialectical Materialism, the general categories that guided the study were praxis, totality and contradiction. We analyze the categories of content: nationalism, proletarian internationalism, I, II, III and IV editions of the International Workers' Association (1st chapter), the Brazilian scientific production on proletarian internationalism, currently (2nd chapter). Through the methodological resources of interviewing and documentary analysis, we performed the comparative analysis of oral histories, formal organization structures and union documents UNE-SN-CDE, APP-FI and UDPM-PI evidencing the internationalist articulations found (3rd chapter). The results of the study show that there are few, occasional, individualized, discontinuous and sparse internationalist articulation initiatives, materialized in the form of meetings, meetings and participation in seminars and congresses.